2001
DOI: 10.1097/00001813-200104000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of growth of human lung carcinoma cells and induction of apoptosis by a novel phenoxazinone, 2-amino-4,4α-dihydro-4α,7-dimethyl-3H-phenoxazine-3-one

Abstract: Anti-tumor effects of a novel phenoxazinone, 2-amino-4,4-dihydro-4alpha,7-dimethyl-3H-phenoxazine-3-one (Phx), which was synthesized by the reaction of 2-amino-5-methylphenol with bovine hemoglobin, were studied in terms of suppression of the proliferation of human lung carcinoma cells and apoptosis induction. When Phx was added to cultures of the human lung carcinoma cell lines A549 (adenocarcinoma) and H226 (squamous carcinoma), it caused the growth inhibition and the death of these cells. Phx also fragmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…Morphological studies of the cells after treatment with Phx-3 indicated typical features of apoptosis (e.g. chromatin condensation and nuclear fragments), as previously reported (data not shown) (5,6). Although cell growth inhibition was detected in all cell lines, A549 lung adenocarcinoma cells exhibited the most potent growth inhibition in response to Phx-3.…”
Section: Cell Growth Inhibition Of Phx-3 In Various Cancer Cell Linessupporting
confidence: 85%
“…Morphological studies of the cells after treatment with Phx-3 indicated typical features of apoptosis (e.g. chromatin condensation and nuclear fragments), as previously reported (data not shown) (5,6). Although cell growth inhibition was detected in all cell lines, A549 lung adenocarcinoma cells exhibited the most potent growth inhibition in response to Phx-3.…”
Section: Cell Growth Inhibition Of Phx-3 In Various Cancer Cell Linessupporting
confidence: 85%
“…This result is comparable to our previous report on the anticancer activity of Phx-3 against human malignant melanoma G361 cells 11) and on that of Phx-1 against various cancer cell lines. [6][7][8][9][10] We furthermore demonstrated that the growth of mouse malignant melanoma B16 cells transplanted into C57BL/6Cr Slc mice was completely inhibited by the administration of 0.5 mg/kg Phx-3 (Figs. 3, 4).…”
Section: Discussionmentioning
confidence: 99%
“…Phx-1 is produced by the reaction of 2-amino-5-methylphenol with human or bovine hemoglobin. Phx-1 inhibits the proliferation of a variety of cultured cell lines such as human epidermoid carcinoma cells (8), Meth A tumor cells (9), human lung carcinoma cell lines (10), leukemia cell lines K562, HL-60, and HAL-01 (11), human endometrial adenocarcinoma cell lines EN and KLE cells (12). In addition to the in vitro effects, Phx-1 also reduces the growth of tumor cells in mice that are transplanted with the cells (9,11).…”
Section: Introductionmentioning
confidence: 99%